2012
DOI: 10.1021/nn302090t
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar Transport in an Electrochemically Gated Single-Molecule Field-Effect Transistor

Abstract: Charge transport is studied in single-molecule junctions formed with a 1,7-pyrrolidine-substituted 3,4,9,10-perylenetetracarboxylic diimide (PTCDI) molecular block using an electrochemical gate. Compared to an unsubstituted-PTCDI block, spectroscopic and electrochemical measurements indicate a reduction in the highest occupied (HOMO)-lowest unoccupied (LUMO) molecular orbital energy gap associated with the electron donor character of the substituents. The small HOMO-LUMO energy gap allows for switching between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 44 publications
1
60
0
Order By: Relevance
“…As an example, metal complexes can display very low HOMO-LUMO gap and are excellent candidates for achieving ambipolar single molecule field-effect transistors than can be switched between n-type and p-type transport behaviour with a gate voltage. 31 Light controlled metal complexes or the association of complexes with light controlled active units is also promising for conductivity gating. Recently, light-induced modulation of molecular conductance was realized with a porphyrin-C 60 dyad.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, metal complexes can display very low HOMO-LUMO gap and are excellent candidates for achieving ambipolar single molecule field-effect transistors than can be switched between n-type and p-type transport behaviour with a gate voltage. 31 Light controlled metal complexes or the association of complexes with light controlled active units is also promising for conductivity gating. Recently, light-induced modulation of molecular conductance was realized with a porphyrin-C 60 dyad.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, many electro-active properties, such as rectification78, negative differential resistance910 and Coulomb blockade11, have been uncovered, indicative of their promising applications in functional electronic devices. Additionally, external stimuli, such as light1213141516, mechanical force1718, magnetic field1920, electrical field212223 and electrochemical potential2425262728, were introduced to modulate the molecular conductivity and thus to tune the properties of functional molecular devices, thereby significantly driving their development. As attested by the giant magnetoresistance effect2930 and photoelectric cooperation3132, a better synergy between such external stimuli and corresponding fabrication of multi-addressable MTJs may further efficiently advance the field of molecular electronics.…”
mentioning
confidence: 99%
“…In addition to this photochromic property, we previously showed that such a ruthenium/DTE association can also perform electrochemical cyclization of the DTE unit in solution at low potential40, in contrast to organic systems4950. Therefore, since it has been successfully demonstrated that molecular conductance can be respectively tuned by light irradiation121314151644 or electrochemical potential2425262728, we were strongly motivated in the association of these two stimuli in a single electronic device to achieve orthogonally modulated MTJs.…”
mentioning
confidence: 99%
“…Furthermore, in the calculations we assume that at zero bias (V = 0) the HOMO is on resonance with the Fermi energy. Experimentally, this may require the presence of an electrochemical [29][30][31] or electrostatic 32 gate. However, we would like to stress that this assumption represents the ideal case with the highest rectification.…”
mentioning
confidence: 99%